GBE1 Inhibition: Alternative Therapy for Lung Cancer by Altering Glucose Metabolism - Istiqomah, Anisa; Ariani, Yulia; Ari Pujianto, Dwi (Syntax Corporation, 2025)
Lung cancer represents a neoplastic malignancy within pulmonary tissue and is associated with the highest mortality rate attributed to cancer globally. Non-Small Cell Lung Cancer (NSCLC) constitutes the predominant category of lung cancer, accounting for approximately 80-85% of all diagnosed cases, with adenocarcinoma subtyping comprising nearly 40% of NSCLC instances. Despite advancements in surgical techniques and diverse therapeutic modalities, the five-year survival rate remains below 20%, necessitating ongoing research endeavors aimed at the enhancement of lung cancer treatment paradigms. This review investigates the intricate interplay between Glycogen Branching Enzyme 1 (GBE1) and metabolic reprogramming, as well as its interaction with hypoxic environments and subsequent effects on the phenotypic characteristics of lung cancer cells. Hypoxic conditions frequently manifest in solid tumors, including lung cancer, eliciting adaptive responses such as the activation of Hypoxia-Inducible Factor-1 alpha (HIF1α), which subsequently initiates angiogenesis, induces metabolic alterations, and contributes to therapeutic resistance. Glycogen Branching Enzyme 1 (GBE1) serves as a critical enzyme involved in the synthesis of glycogen branching structures. In the context of lung adenocarcinoma (LUAD), GBE1 operates within the downstream signaling cascade of the Hypoxia-Inducible Factor-1 (HIF1) pathway. This review aspires to furnish novel insights into the pathogenesis of lung cancer and to assess the strategic targeting of the HIF1α/GBE1/NF-κB/FBP1 axis as a promising therapeutic approach for LUAD.